How can you manage the knowledge of your projects - Pereira, L.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R.; Santos, R. (International Journal of Business Information Systems, 2023)
This paper has the main objective to present the best ways to manage the knowledge of the projects that your organisation implements and how it can be applied to future projects. Nowadays one of the main competitive factors for an organisation to be succeeded depends on how effectively it can innovate and manage its initiatives. The organisations must measure what it knows and how they transfer their knowledge across the organisation or how the future projects will get the best things that had been applied successfully in the past. This research analyses dozens of methodologies, processes, practices, and systems to present a state of the art and a set of strategies that can be adopted in organisations to improved their continuous learning. The main finding is that is critical for the success of the integration of people, technology, and processes in an embedded way.